Assessment of COVID-19 vaccination refusal among healthcare workers in Ethiopia - Elsa Tesfa Berhe; Adisu Tafari Shama; Mohammed Musa Ahmed; Hailay Abrha Gesesew; Hailay Abrha Gesesew; Paul R. Ward; Teferi Gebru Gebremeskel; Teferi Gebru Gebremeskel (Frontiers Media S.A., 2022)
BackgroundEven though the emergence of the coronavirus disease 2019 (COVID-19) vaccine and the increasing vaccination rates are promising, there are reports of refusal to get vaccinated in a different segment of the population, including health care workers.ObjectiveThis study determines the acceptance/refusal of the COVID-19 vaccination and its predictors among health care workers in Ethiopia.MethodsA cross-sectional survey was conducted among a group of health care workers at different health facilities in Ethiopia. Data were collected from 1 to 30 July 2020. Data were collected from 403 participants through an online Google submission form. Data were entered into Epi-info 7 and exported to SPSS version 20 for analysis.ResultsApproximately 38.5% of the health care workers in the study had refused COVID-19 vaccination. Younger age groups vs. 40 and above years (age 20-24 year [AOR: 0.03, 95% CI (0.00, 0.48)], age 25-29 year [AOR: 0.02, 95% CI (0.00, 0.49)], and age 30-34 year [AOR: 0.04 (0.00, 0.49)] and medical doctors vs. Nurses [AOR: 0.06, 95% CI, (0.01, 0.42)] were reported as risk factors; also, academic working staff vs. hospital staff [AOR: 4.42, 95% CI (1.85, 10.54)] was reported as a protective factor toward refusal of COVID-19 vaccination.ConclusionTwo-fifths of health care workers in Ethiopia were indicated to refuse COVID-19 vaccination, implying a significant barrier to achieving WHO's a target of 70% double vaccination rate by mid-2022.